Tendency in the development of modern genres of journalism - Beldibekova А.; Yertassova Г. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
This article deals with the highlights important trends in the global media system development, along with the accelerated development of modern information technologies. Indeed, this process has an impact on the development of today’s Kazakh journalism. As a result, there have been some changes in the content of the material, genre, and media imaginative features. All newspapers and magazines have created their own websites and internet versions. Radio and television channels also find effective ways to distribute programs on the Internet. All this has reduced the dependence on the information space and time, has expanded its opportunities for efficiency and exchange. As a result, the volume of information capacity significantly increased the media interactive content.